The Effect of Environmental Turbulence and Entrepreneurial Opportunities on Entrepreneurial Intention in Digital MSMES Indonesia - Trisyahputra, Bentarro; Kusumawati , Andriani; Wilopo (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This study aims to: 1) Analyze and explain how the effect of the Environmental Turbulence variable (X) on the Entrepreneurial Opportunities variable (Y1), 2) Analyze and explain how the effect of the variable Environmental Turbulence (X) on the variable Entrepreneurial Intention (Y2), 3) Analyze and explain how the effect of the variable Entrepreneurial Opportunities (Y1) on the variable Entrepreneurial Intention (Y2), 4) Analyze and explain how the effect of the variable Environmental Turbulence (X) on the variable Entrepreneurial Intention (Y2) which is mediated by Entrepreneurial Opportunities (Y1). This study uses explanatory research with the quantitative approach with three variables used in this research which are Environmental Turbulence (X), Entrepreneurial Opportunities (Y1), and Entrepreneurial Intention (Y2). Data collection was obtained through the spread of an online questionnaire on 162 MSMEs who use and have businesses on the Blibli.com platform marketplace in Indonesia. The results of this study confirmed the positive impact of Environmental Turbulence on Entrepreneurial Intention when Entrepreneurial Opportunities as a mediating variable. The result also shows that MSME actors can increase their intention to become entrepreneurs if they provide business opportunities that suit their needs during environmental turbulence.